Charting knowledge co‐production pathways in climate and development. (10th January 2019) - Harvey, Blane; Cochrane, Logan; Van Epp, Marissa
Abstract: Climate change poses significant global challenges. Solutions require new ways of working, thinking, and acting. Knowledge co‐production is often cited as one of the innovations needed for navigating the complexity of climate change challenges, yet how to best approach co‐production processes remains unclear. In this article, we explore the ways in which climate and development researchers are approaching the co‐production of knowledge and grapple with the extent to which the modalities used are reaching their stated potential. Using a multiple case analysis of six examples of successful co‐production, we outline a spectrum of co‐production approaches and outcomes and examine the drivers and challenges to co‐production in practice. Drawing on the case evidence and literature, we propose a heuristic that maps out this spectrum of aims and approaches to co‐production and that could inform reflections on how those planning co‐production processes envision them in practice.